Farm-to-Fork in Agro-Rural Tourism – A Sustainable Concept (Journal of Informatics Education and Research, 2025)
The farm-to-fork concept has become an emerging dimension within agro-rural tourism, reflecting a global shift towards sustainable food systems, experiential travel, and community-based development (Sims, 2009; Bessière, 1998). Based on this fact, the present study attempts to explore the relevance and potential of the integration of different farm-to-fork practices in agro-rural tourism settings, such as on-farm food production, harvesting experiences, traditional cooking, and local culinary engagement, with a special focus on Pune district, Maharashtra (Mishra & Patil, 2018). Rooted in sustainability and authenticity, the farm-to-fork model improves tourist awareness of the rural way of life, enhances the producer-consumer relationship, and fosters the promotion of indigenous food traditions (Boyne et al., 2003; Singh & Bhat, 2020). It aims to investigate the conceptual underpinning of farm-to-fork tourism, challenges, and opportunities of its operation, and assesses its economic, environmental, and socio-cultural feasibility in rural areas (Cabrini, 2017; Gupta & Sharma, 2021). The paper makes use of primary and secondary data to discuss how farm owners adopt sustainable approaches, how tourists perceive such experiences, and how this model contributes to long-term rural development (Lane & Kastenholz, 2015). This chapter also discusses the potential contribution of agro-rural tourism to the development of deeper relationships between tourism consumers and farming communities, the fostering of responsible travel behaviour, and promoting local food systems as a sustainable option compared to the commercialized tourism products (Kline et al., 2016). This exploratory work gives insight into farm-to-fork tourism as one holistic, sustainable framework that supports livelihoods in rural areas, enhances the engagement of tourists, and contributes to cultural and ecological preservation (Pradhan, 2021). The study thus emphasizes that strengthening policy support, increasing community participation, improving infrastructure, and integration of sustainable farming methods are necessary for further development of this model of tourism in regions like Pune (MTDC, 2010).